Entre biocentrismo e antropocentrismo: uma ecologia democrática para o enfrentamento da questão ambiental - Pequeno, Marcos Antônio Pimentel (2014)
The ecological issue is one of the most disturbing and complex problems of our time because it calls into question the future of humanity. This research is the result of a reflection on the philosophical dimension of environmental issues. It has been guided by the central thesis that a democratic ecology is the political option most indicated to create the conditions that can agglutinate some needed alternatives to the confrontation of the above question. Accordingly, the general objective aims to reflect on the range and limits of a democratic ecology with a liberal nature. To accomplish this, we face as central axis of the thesis the controversy between anthropocentrism and biocentrism and its impact on various fields that characterize the complex human-nature relationship, especially in ethical and political levels. The course of this work began, in the first chapter, with a study of the theoretical assumptions of the ecological problem, which sent us to an analysis of the foundations of modernity, exposing its dualistic and anthropocentric face governed by the categoris reason and freedom.Then, the research was directed to the current ecological debate that can be synthesized around the existing controversy between biocentrism and anthropocentrism. Therefore, in Chapter2, we exposed the main authors and environmental trends that can be defined as biocentric. In Chapter3, we presented the "moderate anthropocentric" proposal with democratic and liberal nature contained in the texts of Luc Ferry, Michael Shellenberger and Ted Nordhaus. Finally, in the fourth chapter, it was made a reflection on the various dimensions of the ecological problem: ontological, ethic-political, legal, technological, sociocultural and educational; aiming to demonstrate the validity of our central thesis that recognizes the responsibility as a fundamental ethical category and the importance of education, awareness, the state's role as an environmental manager, and of the technology as auxiliary tools for coping with the afore mentioned problem. We hope, thereby, that our choice of a philosophical reflection, grounded in the perspective of a democratic ecology with a moderate anthropocentric nature, can contribute to the current ecological debate in Brazil, wich is still dominated by a largely biocentric stance.